Happiness: Revising Set Point Theory and Dynamic Equilibrium Theory to Account for Long Term Change - Bruce Headey (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
An adequate theory of happiness or subjective well-being (SWB) needs to link at least three sets of variables: stable person characteristics (including personality traits), life events and measures of well-being (life satisfaction, positive affects) and ill-being (anxiety, depression, negative affects). It also needs to be based on long term data in order to account for long term change in SWB. By including personality measures in the 2005 survey, SOEP becomes the first available dataset to provide long term evidence about personality, life events and change in one key measure of SWB, namely life satisfaction. Using these data, the paper suggests a major revision to the set point or dynamic equilibrium theory of SWB in order to account for long term change (Brickman and Campbell, 1971; Costa and McCrae, 1980; Headey and Wearing, 1989; Lykken and Tellegen, 1996). Previously, theory focused on evidence that individuals have their own equilibrium level or set point of SWB and revert to that equilibrium once the psychological impact of major life events has dissipated. But the new SOEP panel data show that small but non-trivial minorities record substantial and apparently permanent upward or downward changes in SWB. The paper aims to explain why most people?s SWB levels do not change, but why a minority do. The main new result, which must be regarded as highly tentative until replicated, is that the people most likely to record large changes in life satisfaction are those who score high on the personality traits of extraversion (E) and/or neuroticism (N) and/or openness to experience (O). These people in a sense ?roll the dice? more often than others and so have a higher than average probability of recording long term changes in life satisfaction. Data come from the 2843 SOEP respondents who rated their life satisfaction every year from 1985 onwards and then also completed a set of questions about their personality in 2005.
Keywords: I31; Z19; 330; Happiness Research; Theory of Happiness; SOEP